Uncanny companions: kinship, activism, and public health as interdependent modalities of care provision under Greek austerity - Andreas Streinzer (EtnoAntropologia, 2021)
The anthropology of the economic crisis since 2007/ 08 analyses the emergence of solidarity practices among social movements, kinship, and friendship during austerity and the recession in Southern Europe. Analysing these practices alongside “resilience” allows to critically examine the interdependence of “variegated austerity” and the normative appraisal of solidarity networks and familial care practices. The article does so by proposing a 'social autopsy' of the configurations of care around an interlocutor who died in 2015 in a public hospital in Greece. The article reconstructs the symbolic and material aspects of gendered obligations, alternative economies, and austerity in public health in how his daughter Kalypso organised care in his last weeks. This analysis aims to contribute to foregrounding these uncanny compansionships when analysing uncertainty and resilience.